Hospital nurse leaders' experiences with digital technologies: A qualitative descriptive study. (27th October 2022) - Laukka, Elina; Hammarén, Mira; Pölkki, Tarja; Kanste, Outi
Abstract: Aim: To describe hospital nurse leaders' experiences with digital technologies. Design: A qualitative descriptive study. Methods: Semi‐structured focus group interviews in one university‐affiliated hospital in Finland. Data were collected from October to November 2021 and analysed using content analysis an e‐leadership framework. Results: A total of 20 frontline nurse leaders and middle‐managers participated. Leaders had different kinds of experiences that concerned their traits, cognition, affect and behaviour with digital technologies. Leaders experienced that they needed to be open‐minded towards digitalization, which sometimes eased their work by making it more efficient. Occasionally, they also got frustrated with digitalization, which caused them stress. Leading digital technologies required collaboration with several different stakeholders, and leaders were especially responsible for ensuring nurses' digital competence. Also, leaders own digital capability was highlighted, although some leaders experienced that their digital capability was low. Conclusion: The e‐leadership framework is useful for describing the conduct of leadership roles in the context of digital services. Digitalization has transformed leadership, yet nurse leaders' education and training do not seem to have been sufficiently modified to these rapid changes. In addition, more attention should be given to how nurse leaders can be distressed by digitalization. Impact: This study provides insight into leadership in the context of digitalized specialized medical care based on nurse leaders' direct statements. Furthermore, the results highlight nurse leaders' educational needs concerning digitalization. Adequately educating nurse leaders to become e‐leaders is crucial to successful digitalization in the nursing domain. Patient or Public Contribution: The study focused on nurse leaders' experiences.